2001
DOI: 10.1155/s1357714x01000184
|View full text |Cite
|
Sign up to set email alerts
|

Primary Leiomyosarcoma of the Adrenal Gland

Abstract: We report a rare case of a primary leiomyosarcoma of the adrenal gland. A 73-year-old woman presented with an inferior vena cava syndrome. MR imaging was suggestive of a large tumour originating from the right adrenal gland. Angiography revealed a tumour vascularised by the right adrenal artery. At explorative laparotomy a tumour of 27 cm in diameter was found which was completely fixed to the liver; the tumour was therefore considered unresectable. As a consequence of the mechanical problems caused by this la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 13 publications
1
31
0
3
Order By: Relevance
“…Twenty cases have been reported in the English literature since 1981. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Typically, the disease presents as a symptomatic retroperitoneal mass more than 10 cm in diameter. It can be associated with a mass effect on surrounding organs, involvement of the inferior vena cava (IVC) by a tumor thrombus, local organ invasion or distant metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty cases have been reported in the English literature since 1981. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Typically, the disease presents as a symptomatic retroperitoneal mass more than 10 cm in diameter. It can be associated with a mass effect on surrounding organs, involvement of the inferior vena cava (IVC) by a tumor thrombus, local organ invasion or distant metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Given the few cases reported in the literature, disease progression and prognosis are difficult to estimate. Tumor size does not seem to be a good predictor of morbidity, as suggested by Etten et al (18), who reported a patient with a 27-cm adrenal leiomyosarcoma without evidence of metastasis on autopsy. Ferrario et al (9) postulated that morphologic grading (presence of mitotic activity, necrotic areas, nuclear atypia) can be predictors of survival.…”
Section: Discussionmentioning
confidence: 88%
“…Some studies have reported that radiation therapy is particularly important in cases where a large tumor locally redevelops or a tumor is located at a site that makes its complete removal difficult [12][13][14]. Doxorubicin and ifosfamide have been the most effective chemotherapy for soft tissue sarcomas in monotherapy and combination therapy for the past 4-5 years.…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy was not used in this case, but its use in cases of localized recurrence has been reported to be effective. It is possible that its use in addition to chemotherapy should also have been considered in the treatment of our patient [12][13][14].…”
Section: Discussionmentioning
confidence: 99%